Analysis of Nursing Students' Knowledge Level Regarding Correct Patient Identification - Hutagaol, Nova Elisabeth; Elon, Yunus (Jurnal Biologi Tropis, 2025)
Patient safety is a crucial aspect of healthcare. Errors in patient identification can lead to serious consequences, such as administering the wrong medication or performing inappropriate medical procedures. Therefore, adequate knowledge of patient identification procedures is crucial for prospective healthcare professionals. This study aimed to analyze nursing students' knowledge of correct patient identification processes and how this knowledge can contribute to improving patient safety in the practice environment. The study found that nursing students at Universitas Advent Indonesia had a fairly good level of knowledge of correct patient identification procedures, with the majority of respondents demonstrating adequate understanding. Knowledge of correct patient identification is closely related to the implementation of patient safety principles, which is a crucial step in reducing the risk of medical errors and improving the quality of healthcare. The results of this study emphasize the importance of continuous education and training on patient identification in the nursing curriculum, so that students not only understand the theory but are also able to apply it practically in nursing care. Conclusion, nursing students' knowledge of correct patient identification is in the fairly good category. This study provides an important contribution to the development of learning strategies and improving student competency in patient safety, particularly correct patient identification.